UPAYA PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN DENGAN STRATEGI MEDIA KARTU KATA SISWA KELAS 1 MI YASPI 6 BAYEMREJO TAHUN PELAJARAN 2022/2023 - Putra Azharin, Barrin (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2023)
Efforts to improve initial reading skills by applying word card media to grade 1 students of MI YASPI 6 Bayemrejo. The purpose of this study was to find out 1) Initial reading skills, 2) Efforts to improve initial reading skills, 3) Application of word card media. The method used in this study is qualitative research. Data collection techniques use interview, observation and documentation techniques. Based on the results of the study, it is known that the initial reading ability using word card media in grade 1 MI YASPI 6 Bayemrejo students has increased compared to before using the media and entered with GOOD criteria. The difficulty faced by students during reading is in distinguishing letters, reading with pronunciation and intonation that is not correct. This is due to lack of reading experience as well as lack of motivation to read the beginning.